ANALISIS KORELASI NILAI SPF DAN KANDUNGAN SENYAWA POLIFENOL TOTAL EKSTRAK BUNGA ROSELLA (Hibiscuss sabdariffa L.) DAN TELANG (Clitoria ternatea L.) - Fitri, Hidayah Anisa; Shafiyatun, Arina Nur Nida; Utami, Pri Iswati (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Excessive and persistent sun exposure containin UV B radiation to the skin causes both acute and chronic sunburn. Polyphenol compounds contained in red rosella extract (ER1), purple rosella extract (ER2) and telang (ET) extracst have photoprotective activity toward UV including UV B. This study aimed to determine their SPF value, total phenolic content (TPC) and their total flavonoids content (TFC) in vitro and to analyze the correlation between the three parameters. In vitro test was performed by UV-Vis spectrophotometry method and correlation was analyzed statistically using two-tailed pearson, graphic plotting and r-value analysis. Results showed that in 0,8% concentration, ER1 and ER2 having maximum SPF values, while ET having ultra SPF value. There was a very strong relationship between SPF, TPC and TFC in the extracts and all of them dependent in concentration. The higher concentration of extract used, the higher the number of TPC, TFC and SPF value. The photoprotective mechanism towards UV B light of ER1 and ER2 were likely contributed by their TPC, but it was both TPC and TFC for ET.